The NAC transcription factor ATAF2 promotes ethylene biosynthesis and response in Arabidopsis thaliana seedlings. Issue 12 (23rd February 2022) - Peng, Hao; Phung, Jessica; Stowe, Evan C.; Dhingra, Amit; Neff, Michael M.
Abstract : Arabidopsis thaliana activating factor 2 (ATAF2) plays extensive regulatory roles in pathogenesis, seedling development, and stress responses. Here, we performed transcriptome analysis on ATAF2 loss‐ and gain‐of‐function mutants to identify differentially expressed genes (DEGs). Gene ontology analyses on DEGs reveal that ATAF2 enhances seedling responses to multiple hormone and stress signals. In particular, our transcriptome analysis suggests that ATAF2 promotes ethylene biosynthesis and responses via activating relevant genes. This novel role of ATAF2 was further demonstrated by using multiple ATAF2 ‐null and overexpression lines for reverse transcription quantitative PCR verification, ethylene production measurements, and assays of seedlings growth responses to the ethylene immediate biosynthetic precursor 1‐aminocyclopropane‐1‐carboxylic acid (ACC). ACC suppresses ATAF2 expression to form a negative feedback regulation loop. Abstract : Transcriptome, gene expression, hormone measurement, and seedling growth response analyses of loss‐ and gain‐of‐function mutants demonstrate that Arabidopsis thaliana NAC transcription factor ATAF2 promotes ethylene biosynthesis and responses via activating biosynthetic genes ACC SYNTHASE 4/ACS5 and responsive genes ERF023 / ERF113 . The ethylene immediate biosynthetic precursor ACC suppresses ATAF2 expression to form a negative feedback regulation loop.